2014
DOI: 10.4314/star.v3i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of <i>Ramalina conduplicans</i> Vain. (Ramalinaceae)

Abstract: Article InformationThe members of the genus Ramalina (Ramalinaceae) are fruticose lichens growing on various types of substrata. The present study was conducted with an aim of determining antimicrobial activity of Ramalina conduplicans Vain. The powdered lichen material was extracted sequentially using petroleum ether, ethyl acetate and ethanol. The solvent extracts were screened for antibacterial activity by Agar well diffusion assay against 15 bacteria which included reference strains and isolates from burn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Hence, alternatives to several synthetic fungicides currently in use are needed. It has been shown that lichen and lichen forming fungi exhibit marked antifungal activity against a wide range of phytopathogenic fungi (Shahi et al, 2001;Oh et al, 2006;Wei et al, 2008;Goel et al, 2011;Tiwari et al, 2011;Kambar et al, 2014a). In the present study, we screened the potential of extract of P. cristiferum and D. applanata to inhibit fungi.…”
Section: Antifungal Activity Of Lichen Extractsmentioning
confidence: 95%
“…Hence, alternatives to several synthetic fungicides currently in use are needed. It has been shown that lichen and lichen forming fungi exhibit marked antifungal activity against a wide range of phytopathogenic fungi (Shahi et al, 2001;Oh et al, 2006;Wei et al, 2008;Goel et al, 2011;Tiwari et al, 2011;Kambar et al, 2014a). In the present study, we screened the potential of extract of P. cristiferum and D. applanata to inhibit fungi.…”
Section: Antifungal Activity Of Lichen Extractsmentioning
confidence: 95%
“…The study of Vivek et al (2014a) showed the inhibitory effect of three Parmotrema species against Gram positive and Gram negative bacteria. Similarly, studies by Karthikaidevi et al (2009), Karagöz et al (2009), Ranković et al (2010), Paudel et al (2012), Pavithra et al (2013), Kekuda (2014), Kambar et al (2014a) and Anjali et al (2015) showed the antimicrobial efficacy of lichens. …”
Section: Antibacterial Activity Of Lichen Extractsmentioning
confidence: 99%
“…Vivek et al (2014b) found antifungal effect of extract of three Parmotrema species against Sclerotium rolfsii (isolate from foot rot of finger millet) and Helminthosporium sp., Alternaria sp., and Aspergillus flavus isolated from moldy grains of sorghum. In a study by Kambar et al (2014a) and Kekuda et al (2014), marked inhibition of Colletotrichum capsici was exhibited by extracts of macrolichens. Vinayaka et al (2014) showed the potential of extract of Usnea pictoides to inhibit the mycelial growth of F. oxysporum f.sp.…”
Section: Antifungal Activity Of Lichen Extractsmentioning
confidence: 99%
See 2 more Smart Citations